2017
DOI: 10.1089/jmf.2017.0001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gymnema sylvestre Administration on Metabolic Syndrome, Insulin Sensitivity, and Insulin Secretion

Abstract: Gymnema sylvestre is a medicinal plant whose consumption has demonstrated benefits on lipid and glucose levels, blood pressure, and body weight (BWt). The aim of this study was to evaluate the effect of G. sylvestre administration on metabolic syndrome (MetS), insulin secretion, and insulin sensitivity. A randomized, double-blind, placebo-controlled clinical trial was carried out in 24 patients (without pharmacological treatment), 30-60 years old, with diagnosis of MetS in accordance with the modified Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…The GAs rich gymnema extract has been used in 97 humans for treating diabetes and obesity (Baskaran et al, 1990;Porchezhian and Dobriyal, 98 2003;Leach, 2007). A recent clinical study confirmed the traditional use of G. sylvestre for 99 diabetes(Zuniga et al, 2017). We have shown that GAs inhibit the growth of hyphae 100 (polarized growth) without affecting the yeast form of growth (isometric growth) 101(Vediyappan et.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The GAs rich gymnema extract has been used in 97 humans for treating diabetes and obesity (Baskaran et al, 1990;Porchezhian and Dobriyal, 98 2003;Leach, 2007). A recent clinical study confirmed the traditional use of G. sylvestre for 99 diabetes(Zuniga et al, 2017). We have shown that GAs inhibit the growth of hyphae 100 (polarized growth) without affecting the yeast form of growth (isometric growth) 101(Vediyappan et.…”
mentioning
confidence: 67%
“…including lowering blood glucose activity in diabetic patients and reducing obesity 402 (Porchezhian and Dobriyal, 2003;Leach, 2007;Zuniga et al, 2017). 403 404…”
Section: Introduction 48mentioning
confidence: 99%
“…The GA-rich gymnema extract has been used in humans to treat diabetes and obesity (Baskaran et al, 1990; Porchezhian and Dobriyal, 2003; Leach, 2007). A recent clinical study confirmed the traditional use of G. sylvestre for diabetes (Zuniga et al, 2017). Since S. gordonii and other oral bacteria use C. albicans hyphae for their attachment (Bamford et al, 2009) and GAs block the hyphal growth of C. albicans , we wanted to test the hypothesis that prevention of C. albicans hyphal growth using GAs could abolish bacteria – C. albicans interactions and the formation of mixed biofilms.…”
Section: Introductionmentioning
confidence: 76%
“…GAs are a family of triterpenoid saponin compounds which are the major active principles of G. sylvestre plant leaves. The extract of this plant is widely used for its various medicinal properties, including lowering blood glucose activity in diabetic patients and reducing obesity (Porchezhian and Dobriyal, 2003; Leach, 2007; Zuniga et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As such, human intervention studies in which Gymnema preparations were administered to those suffering from glucose intolerance and diabetes mellitus (both insulin dependent and non‐insulin dependent), with or without concomitant administration of antidiabetic drugs, were also evaluated for the safety of the preparations (e.g. Baskaran et al., ; Shanmugasundaram et al., ; Al‐Romaiyan et al., ; Zuniga et al., ). Furthermore, studies on the effects of formulas containing G. sylvestre in combination with other herbs and/or micronutrients were also studied for potential toxicity (e.g.…”
Section: Description Of Work Programmementioning
confidence: 99%